El funcionamiento y evaluacion economica de las plantas de secado natural de yuca en la campana 1983-84 - Ospina Patiño, Bernardo (International Center for Tropical Agriculture, 1984)
The operation and economic evaluation of the 7 cassava natural drying plants, established on the Colombian Atlantic Coast, are described for 1983-84. With a total drying floor area of 4000 square meters, 2395 t fresh cassava were processed to produce 946 t dry cassava (2:53:1). The av. occupation of the plants was satisfactory; those affected by rains and mechanical damages showed less than 90 percent occupation. The main problems faced by the plants in terms of infrastructure, equipment, and tools, as well as those relevant to farmer organization and institutional support, were assessed. The economic evaluation covered operational costs (maintenance, administration, labor, fuel, transportation, raw material, banking costs, and others) and an analysis of the economic profitability of each plant. The price paid for fresh cassava was the main factor determining both operating costs and profitability. Increasing the installed capacity of the plants would improve the economic results, but only if the plants operate at over 90 percent occupation efficiency. Training of plant management appears to be critical for efficient plant operation. Cassava var. of inferior quality (reduced DM) should have a reduced price. In general, cassava natural drying was highly profitable under the prevailing conditions. (CIAT)